Brazil, Social Accounting Matrix (SAM), 1995-1996: Aggregated Version - International Food Policy Research Institute (International Food Policy Research Institute, 2003)
The aggregated and disaggregated Brazil Social Accounting Matrices for 1995-96 are primarily based on the 1995 Input-Output Table and National Accounts for Brazil, as well as the 1995-96 Agricultural Census. The disaggregated SAM has a total of 119 accounts. This SAM is characterized by its disaggregation of agricultural production activities by region (Amazon, Northeast, Center-west, and South and Southeast) and farm size (small and large). The aggregated version is based on the disaggregated SAM. It has a total of 71 accounts; agricultural activities and factors are not disaggregated by region. For a description of the construction and use of these SAMs, see Research Report #129, Balancing Agricultural Development and Deforestation in the Brazilian Amazon.